Genetic and Physiological Control of Serine and Glycine Biosynthesis in Saccharomyces - Ulane, Rodney (1972)
Two of the three known metabolic pathways to serine and glycine have been shown to be present in prototrophic yeast strains, i.e., the phosphorylated pathway from glycolytic intermediates and the glyoxylate pathway from tricarboxylic acid cycle intermediates. Two serine-glycine auxotrophs (ser1 and ser2) were found to be blocked in the phosphoglycerate pathway. The ser1 gene controls l-glutamate:phosphohydroxypyruvate transaminase biosynthesis, and the ser2 gene controls phosphoserine phosphatase biosynthesis. The other pathway to glycine, from isocitrate, is repressed by growth in glucose media, specifically, at isocitrate lyase and at the alanine:glyoxylate transaminase. This pathway is derepressed by growth to stationary phase in glucose media yielding high activity of these enzymes. The phosphorylated pathway appears to be the principal biosynthetic pathway to serine and glycine during growth on sugar media. Strains which are serine-glycine dependent in glucose media became capable of serine-glycine independent growth on acetate media. These results describe a method of physiological control of a secondary metabolic pathway allowing a single lesion in the principal biosynthetic pathway to produce auxotrophy. This may be termed conditional auxotrophy.